REVIEW: MEDICAL CONSUMABLE LOGISTIC MANAGEMENT PROCESS IN HOSPITALS - Rachel Karimah; Chriswardani Suryawati; Septo Pawelas Arso (Medical Sains : Jurnal Ilmiah Kefarmasian, 2022)
Medical consumable supply management is done in a continuous cycle, or a logistics cycle, in accordance with the goals of logistics management. The planning, budgeting, purchasing, storing, distributing, withdrawing, destroying, and controlling of the requirements come first. Logistics management strongly emphasize inventory and material movement from the point of origin to consumption to satisfy the demands of consumers and users. In other words, the logistics system aims to provide the most excellent service while minimizing costs. Inventory is a vital component of every organization such as hospital. This study aims to understand the management procedure in the hospital installation's logistics unit. The study used a narrative review methodology. The publications compiled for this study were found using the keywords "Logistics Management," "Hospital Logistics Management," "Medical Consumables," and "Logistics Management" in Scopus, Science Direct, ProQuest, SpringerLink, Google Scholar, and Emerald Insight. Consumable healthcare supplies the amount of the materials used was 11 articles. The findings demonstrate the significance of each element to the operation of logistics management. The study's findings indicate that the logistics management process for managing medical consumables has an impact and can serve as a model for the distribution management system for managing medical supplies based on supply chain management evaluations.